The Correlation Between Thyroid Function, Frontal Gray Matter, and Executive Function in Patients With Major Depressive Disorder - Zhao, Shuai; Xia, Yi; Huang, Yinghong; Zou, Haowen; Wang, Xumiao; Chen, Zhilu; Zhou, Hongliang; Han, Yinglin; Tang, Hao; Yan, Rui; Yao, Zhijian; Lu, Qing (Frontiers in Endocrinology, 2021)
Background: The present study was aimed to investigate the relationships between serum thyroid hormones (THs), frontal gray matter (GM) volume, and executive function (EF) in selected patients with major depressive disorder (MDD). Methods: One hundred and four MDD patients and seventy-five healthy controls (HCs) were subjected to thyroid-stimulating hormone (TSH), free Triiodothyronine (fT3), free Thyroxine (fT4), and executive function tests and underwent structural magnetic resonance imaging (MRI). Voxel-based morphometry (VBM) analysis was performed to compare group differences in the gray matter for the frontal lobe. Furthermore, mediation analysis was used to investigate whether GM volumes of the frontal gyrus mediated the relationship between serum THs and EF in MDD patients. Results: We found that MDD patients exhibited significant GM volume reduction in several brain regions, including the left rectus, right middle frontal cortex, and left middle frontal cortex. Serum TSH levels are positively associated with altered patterns of regional GM volume within MFG and EF. Importantly, gray matter in the right MFG was a significant mediator between serum TSH levels and EF. Conclusions: These findings expand our understanding of how THs affect brain structure changes and highlight that THs might be the target hormone for improving cognition in MDD patients.